Pengaruh Financial Influencer, Financial Literacy, Overconfidence Terhadap Keputusan Investasi Cryptocurrency (Study Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Unisma) - Febrillian, Akbar Tri; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ The objective of this research is to decide the influence of financial influencers, financial literacy, and overconfidence on cryptocurrency investment decisions among FEB students. The sample used in this study consists of 88 students. The data collection technique employed in this research is a questionnaire, and the data analysis method used is multiple linear regression analysis. The results of this study indicate that financial influencers and financial literacy have a significant impact on cryptocurrency investment decisions, while overconfidence does not have a significant impact on cryptocurrency investment decisions.Â Keywords: Financial Influencer, Financial Literacy, Overconfindence, Investment Decision, CryptocurremcyÂ